MODEL GATE KEEPER PUSAT PELAYANAN KESEHATAN MASYARAKAT (Studi di Unit Pelayanan Teknis Daerah Kesehatan Masyarakat Ujung Karang Kabupaten Bengkulu Tengah) - Hafiz Hadiwijaya; Alexsander Alexsander; Rahiman Dani (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
Basically, health centers in the BPJS era act as gate keepers. Gate keeper is a concept of a first-level health service system that acts as a provider of basic health services, functions optimally according to its competency standards and provides health services according to medical service standards. The purpose of this study was to analyze how Ujung Karang Health Center plays the role of gatekeeper in the public health service system (Study at the Ujung Karang Public Health Technical Service Unit, Central Bengkulu Regency) and to analyze the obstacles in implementing the gatekeeper model at Ujung Karang Health Center, Central Bengkulu Regency. The approach used in this study is a qualitative approach. This research will be conducted at the Ujung Karang Public Health Technical Service Unit, Central Bengkulu Regency). This UPTD is located on Jalan Bengkulu - Kepahiang, Ujung Karang, Karang Tinggi District, Central Bengkulu Regency, Bengkulu. Data collection techniques used in the study were in-depth interviews, observation, and documentation. This study uses triangulation techniques through three data collection techniques, namely interviews, observations, and documentation. Based on interviews and observations, this study found that the Ujung Karang Public Health UPTD has carried out its function as a gatekeeper in the health service system quite effectively. This role is reflected in the implementation of initial services, patient monitoring, referral systems, and the diversity and quality of services. However, there are still obstacles in terms of limited medical personnel, supporting facilities, limited referral systems, and access to medical personnel training. Therefore, it is necessary to strengthen the capacity of resources to support the optimization of the role of UPTD as the main implementer of first-level health services. Keywords: Gatekeeper Model, Ujung Karang Public Health UPTD